Cranial nerve involvement among COVID-19 survivors - Heidari, Mohammad Eghbal; Nazemi, Pershang; Feizabad, Elham; Beiranvand, Farzaneh; Afzali, Mahdieh (Frontiers in Neurology, 2023)
The COVID-19 disease suddenly appeared in November 2019 and rapidly spread across the globe. COVID-19 causes neurologic symptoms and complications, which may persist even after recovering, in patients. The objective of this research was to determine the involvement of cranial nerves in COVID-19 survivors.This study was a retrospective study. The study was conducted between March and July of 2022. The analysis included 98 patients with a certain positive polymerase chain reaction. Version 19 of SPSS software was utilized for data analysis.The average age of the participants was 40.47 years (8.81). The olfactory nerve was found to be involved in the most cranial nerve involvement (36.7%). Over 20 % of participants had a taste disorder. The findings from the regression analysis indicated that lung involvement and age have a direct and significant relationship with cranial nerve involvement and can serve as its predictors (p = 0.001).It seems that cranial nerve involvement was sustained in COVID-19 patients who survived. In addition, elderly patients or severe illness were more likely to show cranial symptoms. It is necessary to monitor COVID-19 survivors for neurological symptoms.